2012
DOI: 10.3109/14017431.2012.751506
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac troponin I in congenital heart defects with pressure or volume overload

Abstract: The cTnI release is more frequently associated with pressure than volume overload which resolves after treatment in most children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
3
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 26 publications
1
15
3
2
Order By: Relevance
“…Ours is the first study to report on cTnAAbs among anthracycline-exposed cancer survivors. The number of antibody positive patients exceeded the previously reported prevalence of cTnAAb-positivity among children with congenital heart defects (0.7%) or healthy children (0%) (27).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Ours is the first study to report on cTnAAbs among anthracycline-exposed cancer survivors. The number of antibody positive patients exceeded the previously reported prevalence of cTnAAb-positivity among children with congenital heart defects (0.7%) or healthy children (0%) (27).…”
Section: Discussionmentioning
confidence: 61%
“…Our ethical permission did not allow for plasma analyses on the healthy controls and published values were employed (6,19,27). Due to the limited number of patients, we were not able to compare the imaging parameters between those with normal and abnormal biomarker levels.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Specificity (0.54) and sensitivity (0.65) for measuring TnT as outcome predictor beyond 48 h after ASO in our population was low. Minor increases of TnT shortly after ASO can be found in patients even without a new myocardial injury, for example, in patients with reduced renal clearance, as TnT can be elevated during impaired renal function, or in patients with pressure overload or circulating troponin antibodies . In our investigation, circulating troponin antibodies have not been analyzed.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, children with VSDs were found to have much higher levels of TnT and TnI than children with ASDs, and the TnT and TnI levels showed a good positive correlation with the pulmonary-to-systemic blood pressure ratio (Pp/Ps), which suggests that, in addition to ventricular volume overload, right ventricular pressure overload may also damage the myocardium. Accordingly, Eerola et al [16] reported that in CHD, ventricular pressure and volume overload might increase the TnI levels. Moreover, it has been reported that patients with CHD-related PH have increased levels of TnT.…”
Section: Biomarker Of Myocardial Cell Damage: Troponinmentioning
confidence: 98%